(untitled) (Perner’s Contacts, 2011)
Maps of the most important railway tracks and water ways in Germany clearly shows the railway and water transport network. Next, there are described also an important traffic points of the road and an air transport. International airport in Frankfurt with its importance exceeds the area of Germany and it belongs to the most significant traffic points in Europe.